2021
DOI: 10.1038/s41598-021-93901-6
|View full text |Cite
|
Sign up to set email alerts
|

Weakened overturning and tide control the properties of Oyashio Intermediate Water, a key water mass in the North Pacific

Abstract: The western subarctic Pacific exhibits major biological productivity fed by the Oyashio Current and its two source waters: Western Subarctic Water, which supplies nutrients from the subarctic Pacific, and cold Okhotsk Sea Intermediate Water (OSIW), which supplies iron from the Sea of Okhotsk. We created seasonal climatologies of water properties to understand how the long-term trend (~ 50 years) and 18.6-year tidal cycle affect the Oyashio Intermediate Water (OYW). We found that over the trend, decreased OSIW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…As shown in Figures 2a and 2b, the model‐simulated KE (black lines in Figures 2a and 2b; Cherniawsky & Holloway, 1993; Qiu., 2019) is formed at 35°N where the Kuroshio leaves the coast of Honshu Island and characterized by two major meanders at 143°E and 150°E, is consistent with satellite observations. Similarly, the model also reproduces the meridional location of Oyashio Extension (41°N−42°N; dashed lines in Figures 2a and 2b; Qiu., 2019; Mensah & Ohshima, 2021) and its southwest‐northeast titling between 145°E and 155°E. High eddy activity is found in the vicinity of KE (color shading in Figures 2a and 2b), especially in the upstream region east of 150°E (Yang et al., 2018; Yang & Liang, 2018).…”
Section: Data and Validationmentioning
confidence: 98%
“…As shown in Figures 2a and 2b, the model‐simulated KE (black lines in Figures 2a and 2b; Cherniawsky & Holloway, 1993; Qiu., 2019) is formed at 35°N where the Kuroshio leaves the coast of Honshu Island and characterized by two major meanders at 143°E and 150°E, is consistent with satellite observations. Similarly, the model also reproduces the meridional location of Oyashio Extension (41°N−42°N; dashed lines in Figures 2a and 2b; Qiu., 2019; Mensah & Ohshima, 2021) and its southwest‐northeast titling between 145°E and 155°E. High eddy activity is found in the vicinity of KE (color shading in Figures 2a and 2b), especially in the upstream region east of 150°E (Yang et al., 2018; Yang & Liang, 2018).…”
Section: Data and Validationmentioning
confidence: 98%
“…The North Pacific Intermediate Water (NPIW) and the Okhotsk Sea Intermediate Water (OSIW) are characterized by a potential density of around σ θ = 26.8 kg m 3 (e.g., Mensah & Ohshima, 2021;Yasuda, 1997). The Oyashio Intermediate Water, which is a source of the NPIW, had a warming trend on an isopycnal surface of σ θ = 26.8 kg m 3 or larger during 1990-2020, and this trend resulted from the warming and reduction of the OSIW (Mensah & Ohshima, 2021). Meanwhile, Nakanowatari et al (2015) indicated using a numerical model that the northward advection of subtropical water was related to the warming of intermediate water in the northwestern subarctic NP.…”
Section: Isopycnal Advectionmentioning
confidence: 99%
“…Salinity in this isopycnal layer clearly increased west of 170°W in the subarctic region (Figure 13). The North Pacific Intermediate Water (NPIW) and the Okhotsk Sea Intermediate Water (OSIW) are characterized by a potential density of around σ θ = 26.8 kg m −3 (e.g., Mensah & Ohshima, 2021; Yasuda, 1997). The Oyashio Intermediate Water, which is a source of the NPIW, had a warming trend on an isopycnal surface of σ θ = 26.8 kg m −3 or larger during 1990–2020, and this trend resulted from the warming and reduction of the OSIW (Mensah & Ohshima, 2021).…”
Section: Reasons For the Salinity Changesmentioning
confidence: 99%
“…The properties of WSAW, dSCW, and DSW have been defined by Itoh et al (2003) but may have changed significantly between the periods 1930-1990 and 1990-2022. Such is the case, for example, for WSAW (Andreev & Baturina, 2006;Mensah & Ohshima, 2021). We will therefore update the definitions of these water masses for each of the two periods studied in this paper and their combined period .…”
Section: Water Masses Definitionmentioning
confidence: 99%
“…Variability in the sea ice production could also affect OSIW properties as Kashiwase et al (2014) found a significant relationship between sea ice production in the northern Sea of Okhotsk and OSIW temperature. Besides the interannual variabilities, periodic bi-decadal variations of the OSIW or Oyashio water properties have been observed in several studies (Andreev & Baturina, 2006;Itoh, 2007;Mensah & Ohshima, 2021;Ono et al, 2001;Osafune & Yasuda, 2006) and attributed to the 18.6-year cycle of the diurnal tide.…”
mentioning
confidence: 94%